Radiazioni Ottiche Artificiali: dalla stima alla misura / From the AOR estimations to the AOR measurements - Dario, Rita; Uva, Jessica; Di Lecce, Vincenzo (La Medicina del Lavoro, 2012)
Summary«From the AOR estimations to the AOR measurements». Introduction: This paper presents an innovative device for measuring artificial optic radiations (AOR). AOR are required to be measured in accordance with both Italian and European regulations. The traditional measurement methods do not provide a quantitative measurement of the energy affecting the retina and in particular the fovea. Hence, they are not suitable to assess the real risk to the eye. Furthermore traditional methods are not even able to measure the exposure time (in relation to the position of the head with respect to the source). Materials and Methods: The device permits the acquisition of essential information about AOR source direction and position so as to obtain an evaluation of the relative impact on worker’s everyday activity. The device acts as both a wearable personal dosimeter and an instantaneous radiance detector. The main components are: a colour light sensor mounted at the centre of a pair of safety goggles (placed on the same line of the worker’s sight) used to determine AOR intensity; an inertial/position sensor used for measuring head position/movement, and lastly a video camera to localize emission sources and generate the background in augmented reality visualization. The device is connected by means of a thin, flexible cable to a datalogger and/or netbook? for recording data. Results: the experiments were carried out in order to evaluate AOR sources during work activity; the results obtained and duly processed are presented in the paper. Conclusion: the aims are to achieve work place safety zoning so as to distinguish unsafe from safe areas, and not only specific dangerous areas, via analysis and integration of the overlapping pieces of information obtained with the proposed device.RiassuntoIntroduzione: Il lavoro presenta un dispositivo innovativo per la caratterizzazione di sorgenti luminose ai fini della quantizzazione delle Radiazioni Ottiche Artificiali (ROA) presenti. Tale misura ambientale è richiesta sia dalla normativa vigente nazionale che europea. Le metodiche attualmente disponibili non consentono però la misura reale dell’energia incidente sulla retina ed in particolare sulla fovea, né sono in grado di valutare l’effettivo tempo di esposizione e la posizione, in tempo reale, della testa dell’operatore rispetto alla sorgente. Materiali e metodi: Il sistema presentato si comporta sia da dosimetro che da misuratore di radianza per le radiazioni ottiche; lo stesso è montato su un paio di occhiali di sicurezza, ed è in grado di fornire le indicazioni di posizione dell’asse ottico rispetto alla fonte ROA, visualizzando con tecniche di realtà virtuale, i dati necessari alla zonizzazione dell’ambiente. Il dispositivo è dotato di sensore specifico multibanda di luce per il campionamento delle radiazioni ottiche nello spettro della luce visibile, di un sensore di posizione e di una microtelecamera per ricostruire la geometria di esposizione dell’operatore. Risultati: Sono stati effettuati i test in reali ambienti di lavoro e i dati acquisiti ed elaborati sono riportati nell’articolo. Conclusione: l’obiettivo è quello di realizzare la zonizzazione di un posto di lavoro al fine di distinguere aree sicure da aree a rischio attraverso l’integrazione delle informazioni ottenute dal dispositivo proposto.